2019
DOI: 10.1177/0267659119874258
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on outcomes of patients assisted by veno-arterial or veno-venous extra-corporeal membrane oxygenation: 403 patients between 2005 and 2015

Abstract: Introduction: To assess the impact of age on early outcomes and mortality in veno-arterial extra-corporeal membrane oxygenation and veno-venous extra-corporeal membrane oxygenation recipients, and to investigate predictors of mortality. Methods: Single-center retrospective study on prospectively collected data including all patients treated by veno-venous extra-corporeal membrane oxygenation and veno-arterial extra-corporeal membrane oxygenation (January 2005-July 2015). Outcomes were compared among two subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…As observed in other diseases, older patients receiving ECMO have a poorer prognosis than younger patients, without evidence of age threshold effect [51–53] . However, the impact of age on short-term and long-term prognosis in patients undergoing ECMO may not be independent but rather confounded by comorbidities, clinical presentation, and additional unidentified factors [54–57] .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As observed in other diseases, older patients receiving ECMO have a poorer prognosis than younger patients, without evidence of age threshold effect [51–53] . However, the impact of age on short-term and long-term prognosis in patients undergoing ECMO may not be independent but rather confounded by comorbidities, clinical presentation, and additional unidentified factors [54–57] .…”
Section: Resultsmentioning
confidence: 92%
“…As observed in other diseases, older patients receiving ECMO have a poorer prognosis than younger patients, without evidence of age threshold effect. [51][52][53] However, the impact of age on short-term and long-term prognosis in patients undergoing ECMO may not be independent but rather confounded by comorbidities, clinical presentation, and additional unidentified factors. [54][55][56][57] Accumulated evidence suggests that biological age itself is less useful for guiding the patient selection for urgent ECMO use in the situation of cardiogenic shock.…”
Section: Other Factorsmentioning
confidence: 99%
“…Extremely old patients are generally not regarded as eligible for such invasive procedures. 12,13 The no-ECMO group also had higher proportions of dementia and cancer, which might have been considered "terminal" at the responsible physician's discretion. However, all these factors were T A B L E 4 In-hospital complications and outcomes of COVID-19-associated ARDS according to the use of extracorporeal membrane oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…First, the no‐ECMO group had the highest mean age, potentially implying that ECMO was more likely to be initiated in patients who were perceived viable. Extremely old patients are generally not regarded as eligible for such invasive procedures 12,13 . The no‐ECMO group also had higher proportions of dementia and cancer, which might have been considered “terminal” at the responsible physician's discretion.…”
Section: Discussionmentioning
confidence: 99%
“…Age is associated with increased mortality risk in both adult and pediatric ECMO patients (36)(37)(38)(39). Dalton et al (3) reported that age did not impact survival in pediatric ECMO, yet age was associated with bleeding and thrombosis.…”
Section: Discussionmentioning
confidence: 99%